2017
DOI: 10.1007/s00018-017-2625-7
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization leads to changes in APP (amyloid precursor protein) trafficking mediated by LRP1 and SorLA

Abstract: Proteolytic cleavage of the amyloid precursor protein (APP) by α-, β- and γ-secretases is a determining factor in Alzheimer's disease (AD). Imbalances in the activity of all three enzymes can result in alterations towards pathogenic Aβ production. Proteolysis of APP is strongly linked to its subcellular localization as the secretases involved are distributed in different cellular compartments. APP has been shown to dimerize in cis-orientation, affecting Aβ production. This might be explained by different subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 77 publications
1
53
0
Order By: Relevance
“…For example, APP can dimerize and transmembrane domain amino acid residues critical for this (and affecting γ-secretase cleavage) are mutated in EOfAD ( Yan et al, 2017 ) ( Figure 2 ). The dimerization of APP affects its interaction with the protein SORL1 and this influences the trafficking of APP from the ER to the plasma membrane ( Eggert et al, 2017 ) where FPN1 acts to export Fe 2+ . The most severe EOfAD mutations in APP (those with the earliest Alzheimer’s disease onset ages) affect the transmembrane domain amino acid residues critical for dimerization ( Figure 2 ).…”
Section: Cellular Iron Homeostasis and The Eofad Mutations Of mentioning
confidence: 99%
“…For example, APP can dimerize and transmembrane domain amino acid residues critical for this (and affecting γ-secretase cleavage) are mutated in EOfAD ( Yan et al, 2017 ) ( Figure 2 ). The dimerization of APP affects its interaction with the protein SORL1 and this influences the trafficking of APP from the ER to the plasma membrane ( Eggert et al, 2017 ) where FPN1 acts to export Fe 2+ . The most severe EOfAD mutations in APP (those with the earliest Alzheimer’s disease onset ages) affect the transmembrane domain amino acid residues critical for dimerization ( Figure 2 ).…”
Section: Cellular Iron Homeostasis and The Eofad Mutations Of mentioning
confidence: 99%
“…Although multiple post-translational modifications, including phosphorylation ( 20 ), ubiquitination ( 21 , 22 ), and palmitoylation ( 23 ), regulate functions of sortilin, the mechanisms controlling sortilin trafficking have yet to be fully understood. Because the trafficking of receptors, such as G-protein–coupled receptors ( 24 ) and type I transmembrane proteins ( 25 , 26 ), can be regulated by dimerization, we hypothesized that dimerization is a major regulator of sortilin trafficking to EVs. Here, we provide the first evidence that sortilin forms homodimers, thereby facilitating its trafficking to EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the dimerization may also be accountable for the increase of surface APP after S inhibition. Interestingly, Eggert et al demonstrated that APP homodimers are preferentially located in the endosomes in HeLa cells, and that induced homodimerization reduces surface APP fraction (Eggert et al, 2017a). We postulate that the competition with intracellularly accumulated CTFs after S inhibition reduced APP homodimers and allowed more APP to reach the plasma membrane.…”
Section: Discussionmentioning
confidence: 69%